Pembangunan Desa Berbasis Potensi Lokal Agrowisata di Desa Bumiaji, Kota Batu, Jawa Timur - Ulfah, Irma Fitriana; Setiawan, Andi; Rahmawati, Alfiyatur (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
Rural development one of them to do with the development of local potential. Bumiaji village is a village with a variety of potential agrotourism, ranging from travel picking apples, oranges, pink crystals, flower travel, etawa breeding, and Micro, Small and Medium Enterprises result from the production of agro stretcher. This study examined the theory of sustainable development according to Von Stoker which includes three aspects: ecological, social and economic. The results showed that the process of development in the village Bumiaji has fulfilled the aspects of sustainable development, but in the process is still not able to walk up. Agriowisata potential is the main resource in conducting ecological development. From the social aspect, the potential for ecotourism has provided benefits and impacts to the land owner, the village government and local residents. Bumiaji economic development relies on natural resources and the production of paddy fields. This agro-tourism development can increase people's income and the expansion of the labor force, so that the welfare of the citizens can be increased. Rural development based on local potential agro-tourism should be developed. This can be done through human resource development, promotion and improvement of facilities and infrastructure.